1978
DOI: 10.1136/bjsm.12.4.176
|View full text |Cite
|
Sign up to set email alerts
|

Progressive changes in energy cost during a three-hour race-walk exercise.

Abstract: Twenty experienced race-walkers were exercised in a controlled routine walking at 11.6 km/hr continuously for 3 hr, alternately on a treadmill and a cinder track. Analyses of expired air samples taken at 30 min intervals were used to calculate average R.Q. and energy expenditure. R.Q. was found to decrease progressively from 0.92 to 0.66 in the 3 hr and remained at this level 30 min later. The mean energy cost rose from 46.2 to 55.4 kJ/min or 24.7 to 29.7 kJ/min.m2. The results indicate that this group probabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
2

Year Published

1984
1984
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
2
4
0
2
Order By: Relevance
“…Similar to earlier research (Farley & Hamley, 1979), they found there was an increase in energy cost, but no general alterations in the few gait kinematics measured. However, laboratory-based studies cannot take into account the effects of competition which can have a distinct influence on technique (Knicker & Loch, 1990).…”
Section: Introductionsupporting
confidence: 76%
“…Similar to earlier research (Farley & Hamley, 1979), they found there was an increase in energy cost, but no general alterations in the few gait kinematics measured. However, laboratory-based studies cannot take into account the effects of competition which can have a distinct influence on technique (Knicker & Loch, 1990).…”
Section: Introductionsupporting
confidence: 76%
“…The continuous decrease in performance was most probably due to several different factors such as a high energy deficiency (Bescós et al 2012b ; Knechtle et al 2005 ; Stewart and Stewart 2007 ), an increase in energy cost (Brisswalter et al 1998 ), a continuous depletion of triglyceride and glycogen in skeletal muscles (Enqvist et al 2010 ; Johnson et al 2004 ; Stellingwerff et al 2007 ) and a shift from glycogen to fat as the major energy source (Farley and Hamley 1978 ; Knechtle et al 2003 ). For example, an official finisher in a 24-h ultra-cycling race suffered an energy deficit of ~9915 kcal (Bescós et al 2012b ).…”
Section: Discussionmentioning
confidence: 99%
“…Nella marcia, nel corso della sua storia ultra-centenaria, lo stress fisiologico, così come la spesa energetica (i.e., determinants fisiologici) sono stati ampliamente documentati (Brisswalter, Fougeron & Legros 1998;Farley & Hamley 1978;Hagberg & Coyle 1983;Reilly, Hopkins & Howlett 1979;Yoshida, Udo, Iwai, Muraoka, Tamaki, Yamaguchi et al, 1989). Tuttavia, al fine di comprendere meglio il profilo dello sforzo e la relativa intensità che gli atleti compiono durante le competizioni di marcia (i.e., physiological and regulatory demands) su diverse distanze ufficialmente riconosciute dalla IAAF (i.e., 3 e 5 chilometri indoor; 10, 20 e 50 chilometri outdoor) durante i tre anni del corso di Dottorato di Ricerca si è cercato di incrementare questa conoscenza al fine di migliorare le conoscenze specifiche per poter sviluppare delle strategie di allenamento il più specifiche possibili.…”
Section: Resoconto Dell'attività DI Dottoratounclassified
“…Over its centuries-old history, the physiological stress, energy expenditure or physiological determinants, which are important for RW performances, have been extensively investigated (Brisswalter et al, 1998;Farley et al, 1978;Hagberg et al, 1983;Reilly et al, 1979;Yoshida et al, 1989). However, for understanding the physiological stress imposed on the athletes in real setting, it is also necessary to collect and analyze exercise intensity data during actual competitions.…”
Section: Exercise Intensity and Pacing Strategy Ofmentioning
confidence: 99%